Displacement and energy expenditure prediction of sheep managed with different grazing methods and herbage allowances in natural grassland (Semiárida, 2020)
The Trial was conducted at an 8.4ha natural grassland area, subdivided into 12 experimental units of 0.7 each in the Universidade Federal do Rio Grande do Sul, when were tested two grazing methods (continuous and rotational(CS and RS) and two herbage allowances (HA; 12 and 18 kg dry matter/100 kg live weight; 12 and 18%), resulting in four treatments: CS12, CS18, RS12 and RS18. The displacement was measured during a 24h period using GPS devices fixed on the ewes back. Together with this evaluation was made a grazing behavior evaluation to synchronize the displacement with the grazing activity. With the GPS data (total and grazing displacement) the energy expenditure was predicted using equations reported in the literature. The herbage allowance did not influence the displacement and the estimations of energy expenditure. The CS presented a higher displacement than RS. Under the assumptions of estimations of energy expenditure, a higher level along all day and during grazing would be expected in the CS. Depending of the pasture quality, variations in the grazing methods could become an important management tool.
Keywords: Continuous stocking; GPS; pampa Biome; rotational stocking